Cover Feature: Importance of Mass Transport in High Energy Density Lithium‐Sulfur Batteries Under Lean Electrolyte Conditions (Batteries & Supercaps 5/2022). Issue 5 (6th April 2022) - Li, Shanglin; Ishikawa, Shota; Liu, Jiali; Ueno, Kazuhide; Dokko, Kaoru; Inoue, Gen; Watanabe, Masayoshi
Abstract : The Cover Feature illustrates that high performance lithium‐sulfur battery that can only be achieved under harsh conditions. More information can be found in the Research Article by G. Inoue, M. Watanabe and co‐workers .